Tolerance of physic nut plants to aluminum activity in nutrient solution - Lana, Maria do Carmo; Steiner, Fábio [UNESP]; Zoz, Tiago [UNESP]; Fey, Rubens; Frandoloso, Jucenei Fernando (My University, 2013)
Plants have different levels of tolerance to phytotoxic effects of aluminum and the exploitation of this characteristic is of significant importance to the use of acid soils. This research aimed to evaluate the effect of aluminum activity in nutrient solution on growth of physic nut young plant. After seven days of adaptation, plants were submitted to Al concentrations of 0; 200; 400; 600; 800 and 1,000 μmol L-1, corresponding to Al3+ activity solution, of: 14.5, 21.4; 46.6; 75.6; 108.3 e 144.8 μmol L-1, respectively. The increased activity of Al3+ decreased linearly the number of leaves, plant height, leaf area, shoot dry matter and root length of physic nut plant. Physic nut young plants are sensitive to high aluminum activity in solution. The root length, number of leaves, shoot dry matter and total dry matter were variables more affected by Al activity in solution, and can be used to discriminate the tolerance levels to aluminum in physic nut plants. The accumulation of aluminum increased in a activity-dependent manner; however, its translocation from root to shoot was low.
Tolerância de plantas de pinhão-manso à atividade de alumínio, em solução nutritiva
Keywords: Aluminum absorption; Aluminum toxicity; Exchangeable acidity; Jatropha curcas L